Logistics and transport in the Baltic Sea Region - Ojala Lauri (Centrum Balticum, 2025)
The transport sector in the BSR is significant even in a European context: out of EU-28 total, the transport sector in BSR EU Member States accounts for 27% of all transport and logistics enterprises (311,000 in the BSR), 33% of the turnover (€450 billion), and 34% of employees (10.5 million).
Transport infrastructure investment in Norway is 2 to 2.5 times higher per capita compared to other Nordic countries, and almost 5 times higher compared to all other BSR countries. In Denmark, Sweden, Finland and Germany the expenditure is at 250 to 450 USD per capita, while in other BSR EU Member States and Russia per capita expenditure is around USD 200, with Poland having the highest GDP share of transport infrastructure investments using the 5-year average figures for 2010-2014.
Norway’s per capita transport sector emissions of CO2 (about 28 tonnes/capita) appear to be the highest in the BSR, while the transport sector’s share of all CO2 emissions is the highest in Sweden (over 50%).
Germany (worldwide 1st) and Sweden (3rd) were at the top of World Bank’s Logistics Performance Index (LPI) 2016, followed by Finland (15th), Denmark (17th) and Norway (22nd) out of 160 countries surveyed. Russia was ranked 99th and Belarus 120nd, roughly the level which these two counties have persistently occupied in the LPI. Other BSR countries are found between ranks 29 (Lithuania) and 43 (Latvia).
In the novel Air Trade Facilitation Index (ATFI) and E-Freight Friendliness Index (EFFI), which measure the service performance level of air freight, the top three countries are Sweden, Finland and Denmark, while Russia and Belarus occupy very low ratings. These findings are in line with, for example, the LPI.
The BSR EU Member States occupy the whole spectrum in the EU Transport Scoreboard 2016, which is a comprehensive transport sector composite indicator launched by DG MOVE at the European Commission. It covers the following four policy areas: i) Internal Market; ii) Investment and Infrastructure; iii) Energy Union and Innovation; and iv) People. Out of EU-28, Sweden is rated 2nd, followed by Germany (3rd), Finland and Denmark (both 5th), Estonia (9th), Latvia (13th) and Lithuania & Poland (both 22nd).